2015
DOI: 10.1007/s11325-015-1236-5
|View full text |Cite
|
Sign up to set email alerts
|

CPAP therapy induces favorable short-term changes in epicardial fat thickness and vascular and metabolic markers in apparently healthy subjects with obstructive sleep apnea-hypopnea syndrome (OSAHS)

Abstract: Epicardial fat thickness was associated with OSA severity and may be an additional marker of cardiovascular risk as well as of future diabetes in these patients. CPAP therapy reduced epicardial fat, suggesting its potentially beneficial role in reducing cardiometabolic risk in OSA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
(51 reference statements)
0
23
1
Order By: Relevance
“…Of interest, Parisi et al have pointed out that HF patients with sleep disordered-breathing have higher epicardial adipose tissue (EAT) thickness values than do HF patients without nocturnal apneas [39], which indicates EAT might be a pathophysiological link between OSAS and increased cardiovascular risk [31,33]. Besides, CPAP therapy reduces EAT and significantly ameliorates cardiometabolic parameters in obese OSAS patients [29]. Moreover, EAT is a source of several adipocytokines and directly affects the myocardium through vasocrine and paracrine mechanisms [24].…”
Section: Remodeling and Dysfunction In Osas Patientsmentioning
confidence: 99%
“…Of interest, Parisi et al have pointed out that HF patients with sleep disordered-breathing have higher epicardial adipose tissue (EAT) thickness values than do HF patients without nocturnal apneas [39], which indicates EAT might be a pathophysiological link between OSAS and increased cardiovascular risk [31,33]. Besides, CPAP therapy reduces EAT and significantly ameliorates cardiometabolic parameters in obese OSAS patients [29]. Moreover, EAT is a source of several adipocytokines and directly affects the myocardium through vasocrine and paracrine mechanisms [24].…”
Section: Remodeling and Dysfunction In Osas Patientsmentioning
confidence: 99%
“…Increased fatty acid-triacylglycerol cycling may alter fat distribution - shifting fat from subcutaneous to visceral depots, to the liver, or into circulating lipoproteins. Some [6770] but not other studies [71, 72] have shown regression of visceral adiposity in OSA patients after chronic CPAP therapy. In terms of hepatic fat, OSA is associated with non-alcoholic fatty liver disease [7377].…”
Section: Empirical Datamentioning
confidence: 99%
“…Treatment of OSA with continuous positive airway pressure (CPAP) during 24 weeks significantly reduced EFT in 28 symptomatic OSA patients with AHI > 15, without significant change in BMI or waist circumference(36). Shorter-term of CPAP treatment (3 months) in 25 compliant OSA patients also reduced EFT(159), but in another study EAT remained higher in CPAP treated OSA obese patients (n=19, mean BMI The prognostic impact of EAT reduction by CPAP therapy on cardiovascular outcomes need to be further explored by large prospective studies. In all, EAT is increased in OSA patients and is a correlate of OSA severity.…”
mentioning
confidence: 99%